(untitled) (Revista de Estudios Brasileños, 2017)
This article proposes to analyse some of the main trends related to the contemporary Brazilian chronicle, which here is understood as a hybrid and border genre between journalism and literature. In this way, the chronicle was initially conceptualized as a genre, pointing out its main delimiting characteristics. After this, a brief historical overview of the fixation and the transformations of this genre in Brazil is drawn, which is sometimes considered a “minor genre”, and other times it claims greater attention for itself –especially when it leaves the newspapers and magazines pages (and even from the internet) to occupy a place of greater prominence in collections and books of chronicles. Finally, some texts written by different authors were analysed in order to verify the main trends of the contemporary Brazilian chronicle, especially in the last decades of the 20th century and the first years of the 21st .